Effect of Different Commercial Fertilizers, Harvest Date, and Storage Time on Two Organically Grown Blackberry Cultivars: Physicochemical Properties, Antioxidant Properties, and Sugar Profiles - George Cavender; Mingyang Liu; Javier Fernandez-Salvador; Deborah Hobbs; Bernadine Strik; Balz Frei; Yanyun Zhao (Journal of Food Quality)
Despite increased consumer interest in organic produce, little is known about how different organic production methods affect both the traditional measures of quality and the naturally occurring health promoting (bioactive) compounds of food. In this study, “Obsidian” and “Triple Crown” blackberries (both Rubus hybrids) were cultivated organically and fertilized with either soy meal, fish emulsion/hydrolysate blend, or processed poultry litter fertilizers at a fixed rate. Fruits were hand-harvested three times during their peak production period and stored at 4°C and 85% RH for up to 12 d. Fertilizer effects on the physicochemical properties were minor, while harvest period had a stronger effect, though that trend varied by year. Antioxidant and sugar profile data revealed an interesting pattern: “Obsidian” had ORAC and lower sugar than “Triple Crown” at harvest and also had greater differentiation due to fertilizer treatments. Fertilizer effects differed based on harvest date and cultivar, with late harvest fruit fertilized with fish emulsion fertilizer showing higher TPC and ORAC than other fertilizer treatments, while the early and middle harvest fruit showed similar or greater responses to soy meal-based fertilizer. Time of harvest and length of storage also affected the antioxidant properties and sugar profiles in different ways depending on fruit cultivar, again with the “Obsidian” fruit showing greater variability in general. This study demonstrated that the two cultivars of organically grown blackberry fruit have different physicochemical and antioxidant properties, thus potentially different shelf lives in the fresh market.